2010
DOI: 10.1111/j.1469-7998.2010.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroecology of the host determines microecology of endobionts: protozoal faunas vary with wild ruminant feeding type and body mass

Abstract: Südekum, K H (2011). Macroecology of the host determines microecology of endobionts: protozoal faunas vary with wild ruminant feeding type and body mass. Originally published at: Clauss, M; Müller, K; Fickel, J; Streich, W J; Hatt, J M; Südekum, K H (2011). Macroecology of the host determines microecology of endobionts: protozoal faunas vary with wild ruminant feeding type and body mass. Journal of Zoology, 283(3):169-185. Macroecology of the host determines microecology of endobionts: protozoal faunas vary wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 112 publications
0
13
0
1
Order By: Relevance
“…The evolution of different feeding behaviors in ruminant species has required anatomic, physiologic and microbial gastrointestinal adaptations to their respective dietary niches [2,32]. In accordance with this hypothesis, Clauss et al [33] reported clear effects of the ecology of wild ruminants on the dynamics of their protozoal fauna. In this context, the interaction between tanniniferous plants and browsers likely resulted in greater tolerance to flavonoid compounds than in grazers.…”
Section: Interactionsmentioning
confidence: 91%
“…The evolution of different feeding behaviors in ruminant species has required anatomic, physiologic and microbial gastrointestinal adaptations to their respective dietary niches [2,32]. In accordance with this hypothesis, Clauss et al [33] reported clear effects of the ecology of wild ruminants on the dynamics of their protozoal fauna. In this context, the interaction between tanniniferous plants and browsers likely resulted in greater tolerance to flavonoid compounds than in grazers.…”
Section: Interactionsmentioning
confidence: 91%
“… BM adjusted; # for phylogenetic analyses, Oryx beisa was assigned the position of Oryx leucoryx in phylogenetic tree used Sources: 1 Hofmann (unpublished), 2 (Schmuck, ), 3 (Markgraf, ), 4 (Erdoğan and Pérez, ), 5 (Shao et al, ), 6 (Lönnberg, ), 7 (Clauss et al, ), 8 (Clauss et al, ), 9 (Dittmann et al, ), 10 (Clauss et al, ), 11 (Zerbe et al, ), 12 (Gagnon and Chew, ).…”
Section: Methodsmentioning
confidence: 99%
“…The host and its microbiota are two major components that have co-evolved during millions of years, ensuring an increased fitness and increased chances of mutual survival. The composition of feed is another factor that profoundly influences the microbiota and host physiology (Ley et al, 2008b;Clauss et al, 2011). Herbivory is a successful strategy that has allowed mammals to expand the range of their habitat.…”
Section: The Ruminant Superorganismmentioning
confidence: 99%